2018
DOI: 10.3390/ijms19103001
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin in Serum and Urine of Post-Partum Women with Gestational Diabetes Mellitus

Abstract: Women with a previous history of gestational diabetes mellitus (GDM) have a significantly increased risk of developing type 2 diabetes, obesity, and cardiovascular diseases in the future. The aim of the study was to evaluate ghrelin concentrations in serum and urine in the GDM group in the early post-partum period, with reference to laboratory results, body composition, and hydration status. The study subjects were divided into two groups, that is, 28 healthy controls and 26 patients with diagnosed GDM. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…In our study positive correlations were found between the serum FABP4 and urine ghrelin as well as between the urine FABP4 and serum ghrelin levels in the EGWG group and also between the urine FABP4 and ghrelin levels in the GDM group. Our previous study showed that women with GDM had lower serum and higher urine ghrelin concentrations in the early post-partum period in comparison with the healthy controls, i.e., at 48 h after delivery, yet, these differences were statistically insignificant [2]. On the other hand, there was a positive correlation between the serum and urine ghrelin levels, but only in the healthy mothers.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In our study positive correlations were found between the serum FABP4 and urine ghrelin as well as between the urine FABP4 and serum ghrelin levels in the EGWG group and also between the urine FABP4 and ghrelin levels in the GDM group. Our previous study showed that women with GDM had lower serum and higher urine ghrelin concentrations in the early post-partum period in comparison with the healthy controls, i.e., at 48 h after delivery, yet, these differences were statistically insignificant [2]. On the other hand, there was a positive correlation between the serum and urine ghrelin levels, but only in the healthy mothers.…”
Section: Discussionmentioning
confidence: 98%
“…It seems that this irrelevant difference in favour of greater ghrelin levels in urine might be caused by disturbed metabolism of the circulating ghrelin in GDM mothers. This might have resulted from increased renal ghrelin clearance [2]. Zhang et al demonstrated that overexpression of ghrelin gene via the FABP4 promoter exhibits high plasma concentration of des-acyl ghrelin, alters the development of the white adipose tissues, and improves glucose tolerance and insulin sensitivity [46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It seems that in many ways the pregnancies of women with EGWG resemble pregnancies complicated by gestational diabetes mellitus (GDM). What is important in this context is that the women with a history of GDM exhibit altered risk factors of cardiovascular diseases, including lower HDL concentrations, when compared with mothers with healthy pregnancies [34,35,36].…”
Section: Discussionmentioning
confidence: 99%